Characteristics that identify the organizational culture of the hotel sector in Villa de Leyva, Boyacá (Revista cientifica In Vestigium Ire, 2019)
This work outlines the final results that supported the global development of the framework research called "Management strategies for the construction of an innovation culture, in the hotel sector of Villa de Leyva", assigned to the research group Organizational Projects for the Business Development of the Region - PODER.In order to investigate the elements that identify the existence of an innovation culture in the hotel sector of this highly touristic municipality, it was first necessary to characterize the organizational culture of the sector and its impact on the management processes. This was precisely the objective that guided the research, the results of which are shown in this document, and which had the theoretical, documentary and reference support required by the research question posed and an appropriate methodological design. As a result, the characteristics of the organizational culture of the hotel sector were identified, two types of predominant culture were identified, existing management practices related to the identified culture were described, the relationship between leadership, management and cultural transformation was presented and, finally, the impacts generated by the culture of the sector with respect to administrative management, personal development and the growth of the sector were established.
Keywords: Organizational culture; leadership; innovation; management; hotel sector